멜라토닌 대사를 바탕으로 본 황제내경 소문 사기조신대론 제1장 - 박신영(Shin Young Park); 류호룡(Horyong Yoo); 조정효(Junghyo Cho); 최정은(Jungeun Choi); 박상수(Sangsoo Park); 박미소(Miso S. Park) (동의생리병리학회지, 2023)
This paper aims to reinterpret an ancient Chinese medical book called "The Yellow Emperor's Classic of Medicine" (Hwangjenaegyeong in Korean) from the perspective of melatonin and antioxidant action. In the main body of the paper, we will first explain the changes in circadian rhythms according to the seasons through the first chapter of Somun "Sagijosindaelon". Spring, summer, autumn, and winter are introduced, and their relevance to disease is discussed. Next, the role of the suprachiasmatic nucleus in regulating circadian rhythms in mammals and the synchronization of peripheral clocks with seasonal changes is described. The relationship between light stimulation and melatonin synthesis is then addressed, noting that melatonin synthesis is normally inhibited in the presence of light and produced in the dark. However, recent studies have shown that there are more forms of melatonin that are produced in the presence of sunlight. Finally, it emphasizes the effect of light exposure on the biological clock and the importance of melatonin produced in the mitochondria, suggesting that we should focus on increasing melatonin levels. This paper reinterprets "The Yellow Emperor's Classic of Medicine" from the perspective of melatonin metabolism and provides insights into healthy living.